2017
DOI: 10.1177/1045389x17711817
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and parametric studies of magnetic shape memory alloy–based energy harvester

Abstract: This article presents a model to simulate the behavior of a magnetic shape memory alloy while harvesting vibratory energy. In this type of energy harvester, magnetic shape memory alloy element is placed in the air gap of a ferromagnetic core which conducts the magnetic flux. Two apparent coils are wound around a ferromagnetic core: one to produce bias magnetic field by passing a rectified electric current and the other to serve as an energy pickup coil. Applying compressive time-variant strain field to magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A topological model of deformation twinning in 10M Ni-Mn-Ga crystals is proposed in [75] and a generalized approach for analyzing and modeling twin boundary dynamics is suggested in [76]. A practical application which utilizes MSM model is demonstrated in [77]. In this research MSM based energy harvester model is made, which comprises several minor models including MSM model, electrical and magnetic circuits.…”
Section: Modelingmentioning
confidence: 99%
“…A topological model of deformation twinning in 10M Ni-Mn-Ga crystals is proposed in [75] and a generalized approach for analyzing and modeling twin boundary dynamics is suggested in [76]. A practical application which utilizes MSM model is demonstrated in [77]. In this research MSM based energy harvester model is made, which comprises several minor models including MSM model, electrical and magnetic circuits.…”
Section: Modelingmentioning
confidence: 99%
“…In this stage, a practical example of how to supply this bias stress is provided. In Sayyaadi et al (2018), it is found that the less the length of the air gap is, the more the harvested power is. Thus, the spring-like section should not be in the air gap.…”
Section: Simulationmentioning
confidence: 99%
“…In their work, a harmonic longitudinal strain with a frequency between 130 to 300 Hz is applied on the MSMA specimen. Sayyaadi et al (2018) conducted modeling and simulation of a harvesting system similar to the model of Saren et al (2015). To model the alloy, the thermodynamic-based model of Waldauer et al (2012) is used, which is coupled by a harvester system model in the form of magnetic circuit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results showed the generation of 15 µW power under a base acceleration of 0.3 g RMS at a frequency of 19.1 Hz. Sayyaadi et al obtained the generated power by an MSMAbased energy harvester under the direct application of the sinusoidal force [14]. The MSMA was placed in the air gap of a ferromagnetic core, which conducted the magn etic flux.…”
Section: Introductionmentioning
confidence: 99%